EFEKTIFITAS PENINGKATAN KESADARAN BERIBADAH SISWA MTs 1 AL-FURQON PAMPANGAN KECAMATAN PAMPANGAN KABUPATEN OGAN KOMERING ILIR - Yuniar Wulandari; Muh Misdar; Syarnubi Syarnubi (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2021)
This study examines the effectiveness of increasing worship awareness of students at MTs 1 Al-Furqon Pampangan, Pampangan District, Ogan Komering Ilir Regency. The problem in this study is that there are students who are still not aware of their obligations as Muslims, so when the call to prayer is heard, he is silent, there is no attempt to establish the fardhu prayer. The purpose of this study was to determine the effectiveness of increasing worship awareness of MTs 1 Al-Furqon Pampangan students, Pampangan District, Ogan Komering Ilir Regency. The approach used in this research is qualitative.The focus of this research is the effectiveness of increasing the worship awareness of MTs students. The source of this research data was taken from the research subject, namely students of MTs 1 Al-Furqon Pampangan, Pampangan District, and Ogan Komering Ilir Regency. Data collection techniques using observation, interviews, documentation, and triangulation. Data analysis in this study went through three stages, namely data reduction, data presentation stage, and conclusion stage.The results of this study indicate the effectiveness of increasing religious awareness of students at MTs 1 Al-Furqon Pampangan, Pampangan District, Ogan Komering Ilir Regency. Namely the first type, students whose awareness of praying is good/good with indicators coming to prayer times, praying immediately, often praying in congregation at the mosque, always praying Friday for male students. The second type, students whose awareness of worship is sufficient with indicators of delaying prayer, rarely pray in congregation and pray Friday. And the third type is students with less awareness of worship with indicators of not paying attention to the call to prayer, rarely praying in congregation, and praying Friday. The two supporting factors for increasing the worship awareness of MTs 1 Al-Furqon Pampangan students, Pampangan District, Ogan Komering Ilir Regency, are starting with planning, then continuing with the implementation of learning which begins with the delivery of materials, the use of various methods and media.